Validity Test of an Alternative Method of Quantitative Pain Assessment (MAPKN) in Assessing Intensity of Nociceptive Pain, Mixed Pain, and Neuropathic Pain - Gafur, Rahmi; Susi Aulina; Wuysang, Audry Devisanty; Idris, Irfan; Bahar, Ashari; Hammado, Nurussyariah; Amran, Muhammad Yunus (Journal of Applied Science, Engineering, Technology, and Education, 2023)
Pain is a health problem phenomenon that most often brings patients to see a doctor. Pain intensity is the most often domain which assessed in clinical and research settings. Loeser suggests that four elements need to be considered when evaluating patients with pain. Based on the biopsychosocial approach and the concept of pain from Loeser, a pain assessment was made and called "Alternative Method of Quantitative Pain Assessment (MAPKN)". This study was conducted on 415 pain patients consisting of 163 nociceptive pain, 119 mixed pain, and 133 neuropathic pain. In the nociceptive pain group, MAPKN showed sensitivity 92.59%, specificity 96.43%, AUC 0,959 and a p value <0.001. In the mixed pain group, MAPKN showed sensitivity 98.17%, specificity 80.00%, AUC 0,836 and a p -value of 0.001. In the neuropathic pain group, MAPKN showed sensitivity 92.06%, specificity of 85.71%, AUC 0,951 and a p<0.001. The AUC value of 0.959 (96%) indicates that the diagnostic value of the MAPKN score in assessing pain intensity in the nociceptive pain group is excellent (>90%-100%). AUC value of 0.836 (83%) indicates that the diagnostic value of the MAPKN score in assessing pain intensity in the mixed pain group is good (> 80%-90%). The AUC value of 0.951 (95%) indicates that the diagnostic value of the MAPKN score in assessing pain intensity in the neuropathic pain group is excellent (>90%-100%). This is in accordance with research conducted by Eka Pranata 2004 that MAPKN has strong discriminant validity in assessing pain intensity. MAPKN is valid and has excellent diagnostic value in assessing nociceptive and neuropathic pain intensity, MAPKN is valid and has good diagnostic value in assessing mixed pain intensity.